(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
reveals that 137 respondents opinedthat PRI decision are taken as per rule, i.e. voting system, followed by 34(15.18%) respondents who have no clear idea about the decision making process.While 53 (23.66%) responded that all the decision are taken unanimously.Similarly at the Gram Panchayat level 20 (14.09%) Panches, 4 (26.67%)Sarpanches and 10 (16.95%) Panchayat Samiti members did not response to it. Itmeans they act as a person of just thumb impression or signing on paper aboutthe consensus of final decision taken by other member of the Panchayat.Majority of 99 (69.72%) Panches and 8 (53.33%) Sarpanches opined that all thedecisions are taken as per the rules like casting of vote. 6 (75.00%) ZilaParishad member responded that maximum of decision taken through the process ofcasting vote. So on the basis of above data that decisions are taken either byvoting or by Unanimity.